(untitled) (Research Journal, 2023)
This paper reports the findings of a study that explored the learning difficulties of ethnic students for construction in geometry and analyzed the views and experiences of the students in practicing construction of geometrical figures like triangle and parallelogram with comparing the area of quadrilateral. This study was based on phenomenological research design on exploring the views and experiences of four ethnic minority students. Unstructured interview was used as the main tool for deriving the data from the participants. The collected data were analyzed and interpreted using thematic approach. The results indicated that the students felt conceptual complexity for the learning of geometry. It was found that students had such difficulties due to their irregularity in the geometry classes, teacher’s biasness to the below average students, shyness to ask questions to the teachers and emphasis on culturally privileged students over the minority group of students. Moreover, the ethnic minority students have their own problems as they miss their classes because of socio-economic status of their family and they are confined to their household works. Thus, the study implies that the conceptual complexity and socio-cultural reflection in classroom should be addressed in teaching geometry to the ethnic minority students.